My murder eaudiobook A novel. - Williams, Katie (Books on Tape, 2023)
NATIONAL BESTSELLER  NAMED A BEST BOOK OF THE YEAR BY NPR AND GLAMOUR ! “One of those rare emotionally intelligent books that are also fun reads… Going to keep readers turning pages late into the night.” – The New York Times “Ingenious…fresh and unpredictable.” – The Washington Post “ Gleefully overturn[s] the age-old ‘woman-in-trouble’ plot…eerie and inventive.” –NPR's Fresh Air What if the murder you had to solve was your own? Lou is a happily married mother of an adorable toddler. She’s also the victim of a local serial killer. Recently brought back to life and returned to her grieving family by a government project, she is grateful for this second chance. But as the new Lou re-adapts to her old routines, and as she bonds with other female victims, she realizes that disturbing questions remain about what exactly preceded her death and how much she can really trust those around her. Now it’s not enough to care for her child, love her husband, and work the job she’s always enjoyed—she must also figure out the circumstances of her death. Darkly comic, tautly paced, and full of surprises, My Murder is a devour-in-one-sitting, clever twist on the classic thriller.